Mobile Augmented Reality in Socioscientific Issues-Based Learning: The Effectiveness on Students' Conceptual Knowledge and Socioscientific Reasoning - Annisa, D. N.; Subiantoro, A. W. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2022)
This research investigated the impact of newly developed instructional materials that integrate mobile augmented reality technology called Mobile Augmented Reality of Respiratory System (MARRS) in socioscientific issues-based biology learning. A quasi-experimental research with a nonequivalent pretest-posttest control group design was employed to compare the MARRS and conventional SSI instructional materials using PowerPoint and students' worksheets. Two classes with 72 eleventh-grade students were randomly assigned to experimental or control groups. This research evaluated two outcome variables: conceptual knowledge and socioscientific reasoning. Results indicated no significant difference in the overall conceptual knowledge, but a significant difference was found in socioscientific reasoning between the two groups. Moreover, MARRS is shown to be better in promoting students' analyzing skills and their perspectives and inquiry of socioscientific reasoning. Overall, it can be concluded that MARRS positively impacts being integrated into socioscientific issue-based biology learning.